2020
DOI: 10.3390/ijerph17186743
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Unsafe Behaviors and Traffic Accidents Involving Unlicensed Drivers: A Perspective for Alignment Measurement

Abstract: Road traffic plays a vital role in countries’ economic growth and future development. However, traffic accidents are considered a major public health issue affecting humankind. Despite efforts by governments to improve traffic safety, the misalignment between the policy efforts and on-ground infringements, distractions and breaches reflect the regulatory failure. This paper uses the Bayesian network method to investigate unsafe behaviors and traffic accidents involving unlicensed drivers as a perspective for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
1
5
0
1
Order By: Relevance
“…The findings of the present study come in line with previous research that reported unsafe driving behaviors of young drivers who constitute a high-risk group for traffic accidents, for instance, unsafe driving behaviors of unlicensed young drivers [ 75 , 76 ], risk perception and driving behaviors of young drivers [ 77 , 78 ], and use of mobile phones and infotainment technologies by young drivers while driving [ 79 ]. Furthermore, many researchers confirmed that by using their mobile phones, the drivers were more likely to engage in risky driving behaviors, and were less effective in controlling their lane position, managing their brake reaction time, speed, and headway deviation [ 80 , 81 , 82 ].…”
Section: Resultssupporting
confidence: 91%
“…The findings of the present study come in line with previous research that reported unsafe driving behaviors of young drivers who constitute a high-risk group for traffic accidents, for instance, unsafe driving behaviors of unlicensed young drivers [ 75 , 76 ], risk perception and driving behaviors of young drivers [ 77 , 78 ], and use of mobile phones and infotainment technologies by young drivers while driving [ 79 ]. Furthermore, many researchers confirmed that by using their mobile phones, the drivers were more likely to engage in risky driving behaviors, and were less effective in controlling their lane position, managing their brake reaction time, speed, and headway deviation [ 80 , 81 , 82 ].…”
Section: Resultssupporting
confidence: 91%
“…Driving behavior is influenced by the conditions of the road infrastructure, the built environment, or the weather, but also by individual factors, including the driver's status (driver's license, level of alcohol intake, influence of illegal substances, level of tiredness) or even the attitudes toward driving, which are associated with compliance with safety and speed rules, and risky driving [33][34][35][36].…”
Section: Urban Mobility Against Expected Urban Livabilitymentioning
confidence: 99%
“…Inattentive driving and multitasking are major contributors to road crashes and fatalities with distraction being a common factor in a significant portion of traffic crashes [ 5 , 6 ]. Moreover, previous studies analyzing road crashes associated with distracted driving and multitasking asserted that drawing attention away from driving leads to increased steering variability, lateral position deviation, aggressive braking, and delayed responses [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%